The contribution of the broadcast media in Reputation Repair in Kenyan Healthcare Corporates - Odhiambo, Judy Apondi; Mberia, Dr. Hellen K. (IJRDO-Journal of Applied Science, 2015)
The overall effect of crises is damage to corporate reputation. Reputations are widely recognized as valuable, intangible asset. Reputation being a valuable asset to an organization, when crises occur, there is need for reputation repair. One of the most important stakeholders in reputation repair is the media. The broadcast media can be used to build or restore an organization’s reputation as well it can destroy the reputation of an organization. However, many healthcare corporates have continued to ignore the important contributions that the media plays towards reputation repair. This study thus fills a research gap on how the broadcast media can be used in reputation repair in Kenyan healthcare corporates. The major objective to this study was to establish the impact of the broadcast media coverage in reputation management in Kenyan healthcare corporates. The study used a descriptive survey design which enabled the researcher to get a quantitative and a qualitative insight into the opinions and attitudes of the respondents in different environments that could easily be compared. The population included PRO’s of healthcare corporates, Media practitioners, employees from different healthcare corporates and consumers of healthcare services. The researcher used stratified sampling to select 10 healthcare corporates and thereafter selected 10 PRO’s; 30 employees of the corporates were selected through systematic sampling; 150 consumers of healthcare services were selected through multi-stage sampling while 10 broadcast media practitioners were selected through random sampling giving a study population of 200. The data collected was then analysed by the use of the SPSS (Statistical Package for Social Sciences) package 17.0 and presented in tables, frequencies, pie charts and graphs. The study established that strategies used in reputation repair are usually effective when the media highlights them in their coverage. The study therefore concluded that broadcast media coverage indeed has an impact in reputation repair.